The Genetic Diversity of Bali Sardinella (Sardinella lemuru) Caught at Bali Strait and Its Possible Relation to The Ocean Circulation - Sartimbul, Aida; Hendiari, I Gusti Ayu Diah; Arthana, I Wayan; Kartika, Gde Raka Angga; Winata, Victor Adi; Pranowo, Widodo Setiyo; Susanto, Raden Dwi; Rohadi, Erfan; Muslihah, Nurul; Yona, Defri; Iranawati, Feni (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract Highlight Research A low sequence divergence of lemuru between Bali Strait and the northern latitude. S. lemuru migration route through ITF will maintain its nucleotide variation. The high haplotype diversity of lemuru is a testament to its adaptability. S. lemuru's high haplotype diversity supports their stock recovery in the Bali Strait. Two sardine species are morphologically and genetically highly distinct, even though they prefer overlapping water mass conditions from each other. Abstract Sardinella lemuru is known as the native pelagic fish of the Bali Strait. However, its presence has recently become challenging to find. This study aimed to validate S. lemuru using molecular taxonomy and link it to water circulations for sustainable management. It is the first study of relatively complete sequence data on S. lemuru in the Bali Strait. A total of 47 sequences were amplified using the control region gene of mitochondrial DNA. Other S. lemuru (n = 4) and Amblygaster sirm (n = 12) sequences were retrieved from GenBank. Low sequence divergence is observed in clade-1 of S. lemuru across the Bali Strait, Manado-Sulawesi, and Kudat-Malaysia. This is probably due to its migration using the main Indonesian ThroughFlow (ITF). There is an evolutionary divergence between two groups of S. lemurs, measuring 35.3%±4.1. The first signs of these cryptic groups were found at Canggu and Prigi, with 87 base-pair differences between the two groups. This study also presents strong evidence that A. sirm prefers overlapping water mass conditions with S. lemuru in the Bali Strait but is morphologically and genetically distinct. Notably, three samples of A. sirm in Kedonganan-Bali are clustered with other A. sirm locations passed by the primary and secondary South China Sea throughflow. The high genetic diversity of S. lemuru among Bali Strait sites demonstrates its adaptive ability, with scattered single-frequency haplotypes. The adaptive ability traits of S. lemuru support its stock recovery. The stock recovery recommendation is based on finding S. lemuru’s adaptive traits within their populations in suitable habitats and climatic conditions